Early‐life seasonal, weather and social effects on telomere length in a wild mammal. Issue 23 (27th June 2021) - van Lieshout, Sil H. J.; Badás, Elisa P.; Bright Ross, Julius G.; Bretman, Amanda; Newman, Chris; Buesching, Christina D.; Burke, Terry; Macdonald, David W.; Dugdale, Hannah L.
Abstract: Early‐life environmental conditions can provide a source of individual variation in life‐history strategies and senescence patterns. Conditions experienced in early life can be quantified by measuring telomere length, which can act as a biomarker of survival probability in some species. Here, we investigate whether seasonal changes, weather conditions and group size are associated with early‐life and/or early‐adulthood telomere length in a wild population of European badgers ( Meles meles ). We found substantial intra‐annual changes in telomere length during the first 3 years of life, where within‐individual effects showed shorter telomere lengths in the winter following the first spring and a trend for longer telomere lengths in the second spring compared to the first winter. In terms of weather conditions, cubs born in warmer, wetter springs with low rainfall variability had longer early‐life (3–12 months old) telomeres. Additionally, cubs born in groups with more cubs had marginally longer early‐life telomeres, providing no evidence of resource constraint from cub competition. We also found that the positive association between early‐life telomere length and cub survival probability remained when social and weather variables were included. Finally, after sexual maturity, in early adulthood (i.e., 12–36 months) we found no significant association between same‐sex adult group size and telomere length (i.e., no effect of intrasexual competition). Overall, we show that controlling for seasonal effects, which are linked to food availability, is important in telomere length analyses, and that variation in telomere length in badgers reflects early‐life conditions and also predicts first year cub survival.